Changes in nitrogen metabolism and antioxidant enzyme activities of maize tassel in black soils region of northeast China - Xu, Hongwen; Lu, Yan; Xie, Zhiming; Song, Fengbin (Frontiers in Plant Science, 2014)
Two varieties of maize (Zea mays L.) grown in fields in black soils of northeast China were tested to study the dynamic changes of nitrogen metabolism and antioxidant enzyme activity in tassels of maize. Results showed that antioxidant enzyme activity in tassels of maize increased first and then decreased with the growing of maize, and reached peak value at shedding period. Pattern of proline was consistent with antioxidant enzyme activity, showing that osmotic adjustment could protect many enzymes, which are important for cell metabolism. Continuous reduction of soluble protein content along with the growing of maize was observed in the study, which indicated that quantitative material and energy were provided for pollen formation. Besides, another major cause was that a large proportion of nitrogen was used for the composition of structural protein. Nitrate nitrogen concentrations of tassels were more variable than ammonium nitrogen, which showed that nitrate nitrogen was the favored nitrogen source for maize.